OCENA WŁASNYCH ZDOLNOŚCI UCZNIÓW UZDOLNIONYCH JĘZYKOWO W POLSKICH SZKOŁACH PONADGIMNAZJALNYCH - Sobańska, Joanna (Neofilolog, 2018)
An exceptionally linguistically talented student should have all the predispositions to be multi-linguistic. The reason is that such skills, at least potentially, assume high predispositions to learn all foreign languages. And even though the process of language learning and its efficiency depends on many other factors, one of them is the assessment of one’s skills and potential by the linguistically talented student. The aim of the article is to present convictions of students identified as linguistically talented with respect to their skills and achievements concerning foreign language learning. A large part of the paper deals with the presentation of theoretical aspects related to linguistic skills and a short analysis of selected factors that influence the development of linguistic skills in students, in particular the assessment of own skills and possibilities by students (self-assessment).